Ponzio, a. La Rivoluzione Bachtiniana. Il Pensiero Di Bachtin e l'ideologia Contemporânea. Bari: levante Editori, 1997. 357 p. (Revista Brasileira Multidisciplinar, 2009)
This book review of The Bakhtinian revolution: Mikhail Bakhtin's thought and the contemporary ideology ("La rivoluzione bachtiniana. Il pensiero di Bachtin e l'ideologia contemporanea") by Augusto Ponzio is justified by the modern relevance of this work, which has just been translated into Portuguese. This relevance is also revealed by Ponzio in explaining the work of the Russian Mikhail Bakhtin, who, at the beginning of the twentieth century, wrote literary and philosophical studies that are now opening up a range of analysis in several areas of knowledge, including the ideological dimension. The book is an overview of Bakhtin's work, from the perspective of the philosopher Augusto Ponzio.
Keywords: Mikhail Bakhtin; Philosophy of language; Otherness; Ideology Mikhail Bakhtin; Ideology